First record of the semi-slug Omalonyx unguis (d’Orbigny, 1837) (Gastropoda, Succineidae) in the Misiones Province, Argentina - Guzmán, Leila Belén (2018)
Omalonyx unguis (d’Orbigny, 1837) is a semi-slug inhabiting the Paraná river basin. This species belongs to Succineidae, a family comprising a few representatives in South America. In this work, we provide the first record for the species from Misiones Province, Argentina. Previous records available for Omalonyx in Misiones were identified to the genus level. We examined morphological characteristics of the reproductive system and used DNA sequences from cytochrome oxidase subunit I (COI) gene for species-specific identification. These new distributional data contribute to consolidate the knowledge of the molluscan fauna in northeastern Argentina.